Mapping of Cultural Heritage Buildings in Padang City based on Geographic Information Systems - Aziz Kurniawan; Endah Purwaningsih (Postgraduate School, Universitas Negeri Padang, 2024)
This research aims to analyze heritage buildings in Padang City, focusing on their distribution, condition, ownership status, and identification of buildings that may qualify as cultural heritage sites. The research method employed is quantitative descriptive with a spatial approach, utilizing map analysis and Nearest Neighbor Analysis, leveraging both secondary data and field surveys. The research findings indicate a pattern in the distribution of heritage buildings based on their functions in Padang City. Religious functions are evenly distributed, while social and cultural functions tend to cluster together. Special functions are evenly dispersed, whereas commercial functions are randomly distributed, and residential functions are also evenly distributed. There are three types of damage observed in heritage buildings, ranging from mild to severe, with some already destroyed. The number of heritage buildings and their levels of damage are as follows: 47 buildings with mild damage, 15 with moderate damage, and 9 with severe damage, including 2 that have been destroyed. Additionally, there are 6 buildings suspected to be cultural heritage sites, such as the Mercusuar Sungai Beremas and the Japanese Tunnel on Bukit Lampu, Batu Busuk Kuranji Rotten Rock Hydroelectric Power Plant, Bagindo Aziz Chan Birthplace Museum, Tarok Mosque, Syekh Surau Baru Tomb, and Siti Nurbaya Big House. As a recommendation, the Padang City Government is advised to conduct a comprehensive identification and inventory of all cultural heritage buildings. The distribution data of cultural heritage buildings is available in the form of a Web GIS accessible via the link: https://azizkurniawan-bangunan-cagar-budaya-kota-padang.gis.co.id/.